2013
DOI: 10.1128/iai.01288-12
|View full text |Cite
|
Sign up to set email alerts
|

LL-37 Opsonizes and Inhibits Biofilm Formation of Aggregatibacter actinomycetemcomitans at Subbactericidal Concentrations

Abstract: Host defense peptides are immediate responders of the innate immunity that express antimicrobial, immunoregulatory, and wound-healing activities. Neutrophils are a major source for oral host defense peptides, and phagocytosis by neutrophils is a major mechanism for bacterial clearance in the gingival tissue. Dysfunction of or reduction in the numbers of neutrophils or deficiency in the LL-37 host defense peptide was each previously linked with proliferation of oral Aggregatibacter actinomycetemcomitans which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Other enzymes possibly processed by gingipains have the ability to degrade aggregation factors of A. actinomycetemcomitans, indicating that gingipains are indirectly involved in inhibiting autoaggregation and/or coaggregation of A. actinomycetemcomitans. tion with other species in co-cultured biofilm (Rosen et al, 2003;Periasamy & Kolenbrander, 2009;Sol et al, 2013). The present study showed the results using a non-fimbriated A. actinomycetemcomitans strain.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Other enzymes possibly processed by gingipains have the ability to degrade aggregation factors of A. actinomycetemcomitans, indicating that gingipains are indirectly involved in inhibiting autoaggregation and/or coaggregation of A. actinomycetemcomitans. tion with other species in co-cultured biofilm (Rosen et al, 2003;Periasamy & Kolenbrander, 2009;Sol et al, 2013). The present study showed the results using a non-fimbriated A. actinomycetemcomitans strain.…”
Section: Discussionsupporting
confidence: 70%
“…Some previous studies used non‐fimbriated A.actinomycetemcomitans strains to examine a part of their nature in mono‐cultured biofilm and coaggregation with other species in co‐cultured biofilm (Rosen et al ., ; Periasamy & Kolenbrander, ; Sol et al ., ). The present study showed the results using a non‐fimbriated A. actinomycetemcomitans strain.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, the hallmark of Papillon–Lefèvre syndrome is the aggressive periodontitis. Thus, a lack of serine proteases and neutrophil dysfunction may lead to the outgrowth of periodontal pathogenic bacteria .…”
Section: Cathepsin C Mutations Cause Papillon–lefèvre Syndromementioning
confidence: 99%
“…Reports have shown that patient gingivae harbor Aggregatibacter actinomycetemcomitans preferentially , although some have not detected a specific pathogenic flora . Neutrophil periodontal clearance of A. actinomycetemcomitans employs antimicrobial peptides like the cathelicidin antimicrobial peptide LL‐37 . Recent reports show that proteinase 3 is needed for the generation of LL‐37 from the cathelicidin antimicrobial peptide (hCAP‐18/LL‐37) .…”
Section: Cathepsin C Mutations Cause Papillon–lefèvre Syndromementioning
confidence: 99%
“…Previous studies reported that several neutrophil-derived granule proteins/peptides opsonize bacteria resulting in enhanced phagocytosis. 51,52 With regard to LL-37, it was shown that opsonization of oral Aggregatibacter actinomycetemcomitans with the peptide resulted in increased phagocytosis by murine macrophages, 53 and an uptake of LL-37-coated polystyrene beads by nondifferentiated primary human monocytes was increased compared with uncoated beads. 45 On the other hand, bacterial phagocytosis was also shown to be augmented by pretreatment of macrophages with neutrophil secretion products, 54 including LL-37.…”
Section: 9mentioning
confidence: 99%